Metoda feldenkrais TM - Zmajšek, Lucija (Šport (Ljubljana), 2019)
The aim of the Feldenkrais method is that with the help of trials, the individual discovers new ways of coordinated movements, connects them into a whole and enables the organism to regain the harmony between movement and mind. It is based on mechanical and neurological principles, which we access through simple practical-motion lessons. By incorporating the brain and whole body into simple, yet expressive movements, we redefine the nervous paths and thus begin to move to a more healthy, coordinated and more friendly way. Using the Feldenkrais method, we develop a kinesthetic awareness through a guided lesson with a teacher, which means that through the process we learn a better, optimal way of body movement and body posture. Through guided lessons, we achieve pain reduction, improvement of balance, mobility and walking, reduction of anxiety in elderly people with neurological and musculoskeletal disorders (Hillier and Worley, 2015; Ernest-Canter, 2005). The method can be performed in healthy adults, in people with neurological, respiratory and skeletal muscular disorders, or in a very wide range of people (Ullmann et al., 2010). In the article, we tried to present the Feldenkrais method for several different groups of people - children, business people, pregnant women, and finally present the practical implementation of two exercises from over the two thousand, which we can perform.
Keywords: busines people; children; Feldenkrais method; Feldenkrais metoda; gibalna metoda; kinestetic awerness; kinestetično zavedanje; movement metod; otroci; poslovneži; sport; šport